Pengaruh Budaya Organisasi dan Lingkungan kerja Terhadap Kinerja Kerja Karyawan PT. Prudential Life Assurance - Sulistyawati, Anisha; Siska, Elmira (Jurnal Mahasiswa Kreatif, 2024)
Organisational culture and work environment are important things in companies in developing the performance of their employees, including PT companies. Prudential Life Assurance. The purpose of this research is to determine the influence of organisational culture and work environment on the work performance of employees of the Client Relations Centre department of the Business Partner Relations unit of PT. Prudential Life Assurance. The population of this study was 70 employees of the Business Partner Relations unit of PT. Prudential Life Assurance. The sampling technique used was purposive sampling. From this technique, a sample of 60 was obtained. The research design was a quantitative method. Data was collected by questionnaires sent to employees. Data processing includes validity, reliability, classical assumption tests, partial tests (t), and simultaneous tests (F). The results show that the questionnaire items are valid, reliable, and free from econometrics. Partially, organisational culture has a significant effect on employee performance with a sig result of 0.000 <0x7E> 0.05 and a calculated t value of 3.771 > 2.0274. The work environment has a significant effect on employee performance with a sig result of 0.000 <0x7E> 0.05 and a calculated t value of 4.207 > 2.0274. Simultaneously, organisational culture and the work environment have a significant and positive effect on employee performance, with a sig result of 0.000 <0x7E> 0.05 and a calculated f value of 17.049 > f table 3.16.